Europol review / Europol / 2015 (Europol review general report on Europol activities, 2016)
2015 was a challenging year for Europe and for its law enforcement community. The European Union was faced with an unprecedented influx of irregular migrants. More than one million migrants entered the European Union illegally in 2015. The vast majority of these journeys were facilitated by criminal networks, which have earned huge sums as a result. In response to this situation, Europol reorganised its resources to assist the Member States and face the new security challenges effectively. Europol officers were deployed in hot spots in Italy and Greece, where the assistance was most needed, as part of the new EU Regional Task Force concept. In order to develop its services in this area further, Europol agreed to set up a European Migrant Smuggling Centre at its headquarters, which was launched in February 2016. This, however, has not been the only challenge. The year's start and end were marked by terrorist attacks in Paris, which demonstrated the ambition and capability of the so-called Islamic State to inspire and execute highly organised international attacks. Europol did its utmost to assist the Member States in this difficult time. The Emergency Response Team at Europol supported France and Belgium 24/7 in their counter terrorist operations and providing analysis and delivering significant investigative leads. Europol's databases are now being systematically fed with critical information allowing for even faster and more effective identification of international terrorism links. Europol was also tasked by the Council of the European Union to upgrade its operational capabilities and create a European Counter Terrorism Centre at Europol, which was launched in January 2016. This was preceded by the creation in July 2015 of the EU Internet Referral Unit, responding to the spread of terrorist and violent extremist propaganda online. For Europol these developments meant a dramatic increase in workload, a shift in operational priorities, and an increasing need to work 24/7 to analyse life-saving intelligence and provide crucial investigative leads in real time. This extra effort will continue in 2016. Against this background, Europol continued to fulfil its mission and provide its services in other areas, in particular supporting Member States' concerted efforts to tackle the main serious organised crime threats. In the meantime, Europol has adopted a new Strategy for 2016-2020 which will provide strategic guidelines for the years to come. The legislative process for the adoption of a Europol Regulation also continued, bringing political agreement on the text in December 2015.